(untitled) (Swiss Medical Weekly, 2013)
BACKGROUND: Preventive treatment may avoid future cases of tuberculosis among asylum seekers. The effectiveness of preventive treatment depends in large part on treatment completion. METHODS: In a prospective cohort study, asylum seekers of two of the Swiss Canton Vaud migration centres were screened with the Interferon Gamma Release Assay (IGRA). Those with a positive IGRA were referred for medical examination. Individuals with active or past tuberculosis were excluded. Preventive treatment was offered to all participants with positive IGRA but without active tuberculosis. The adherence was assessed during monthly follow-up. RESULTS: From a population of 393 adult migrants, 98 (24.9%) had a positive IGRA. Eleven did not attend the initial medical assessment. Of the 87 examined, eight presented with pulmonary disease (five of them received a full course of antituberculous therapy), two had a history of prior tuberculosis treatment and two had contraindications to treatment. Preventive treatment was offered to 75 individuals (4 months rifampicin in 74 and 9 months isoniazid in one), of whom 60 (80%) completed the treatment. CONCLUSIONS: The vulnerability and the volatility of this population make screening and observance of treatment difficult. It seems possible to obtain a high rate of completion using a short course of treatment in a closely monitored population living in stable housing conditions.